Building an Exemplary School Brand: Strategic Approaches to Enhancing Student Recruitment - Riska Meisyi Putri; Wahyu Arohman; Nursalimah; Dismawati; Sugimin; Mardalena; Anggia Pratiwi (Al-Qalam Institue, 2026)
This study aims to analyze strategies for building a school brand image to attract prospective students in the context of Islamic secondary education. A qualitative case study approach was employed to gain an in-depth understanding of institutional branding practices. Data were collected through observations, semi-structured interviews, and documentation, and were analyzed using the interactive model of Miles, Huberman, and Saldaña. The analysis was guided by Keller’s Brand Image theory, encompassing the dimensions of strength, favorability, and uniqueness of brand associations. The findings indicate that a positive brand image is developed through consistent academic and non-academic achievements, distinctive religious and character-building programs, qualified teachers, effective use of social media, and support from alumni and the surrounding community. Nevertheless, the institution continues to face challenges, including intense competition among schools, limited effectiveness of digital promotional strategies, insufficient alumni engagement, and persistent public perceptions regarding madrasah education. These findings imply that strengthening strategic branding, expanding digital communication, and fostering sustainable stakeholder collaboration are essential for enhancing institutional competitiveness and increasing prospective students’ enrollment interest in an increasingly competitive educational environment.